Perceptions of free will and self-control in a medically relevant treatment recommendation scenario - Alderson, Courtney; Hagiwara, Nao; Green, Jeffrey (The Journal of social psychology, 2022)
Do provider perceptions of patient free will and treatment related self-control influence treatment recommendations and do such perceptions differ due to race? If so, such bias may be a mechanism for racial disparities in medical treatment recommendations. We hypothesized: (1) greater perceived patient free will would indirectly effect treatment recommendations for patients through increased perceived patient treatment related self-control; (2) participants would perceive greater free will for a hypothetical racial ingroup patient than outgroup patient; and (3) such effect would be exacerbated by greater levels of racial identity and racial bias. A 2 (Participant: Black vs. White) x 2 (Target: Black vs. White) x Continuous (Racial Identity/Racial Bias) between-subjects design supported hypothesis 1. Perceived patient free will predicted more rigorous treatment recommendations treatment related self-control. No evidence was found in support of hypotheses 2 and 3. Using a novel experimental design, this work demonstrates the importance of free will and self-control perceptions.